DEVELOPMENT OF TRANSNATIONAL AND JOINT EDUCATION PROGRAMMES: SCIENTIFIC AND PRACTICAL APPROACHES BASED ON UZSWLU EXPERIENCE AND INTERNATIONAL QUALITY ASSURANCE SYSTEMS - Saloxiddinova Kamola Abduvaliyevna (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In this article, I analyze the process of the joint program based on the Uzbekistan World Language University and the development of transnational education. The international quality recommendation system( ESQ, EQF), the education based on competency, the outcome of education results, and the effect of digital technologies on academic mobility are tested. The research results are suggested to increase the quality of the joint program education.